Changes in operative treatment of tibia fractures in Finland between 2000 and 2018: A nationwide study - Ylitalo Antti AJ; Dahl Kalle A; Reito Aleksi; Ekman Elina (Finnish Surgical Society, 2022)
Introduction:
Incidences of different tibia fractures are not well reported. Possible changes in the operative treatment methods have also not been studied. The aim of this nationwide registry study is to determine the incidence of operatively treated tibia fractures and investigate the possible changes in treatment methods in Finland between 2000 and 2018.
Methods:
All patients aged 16 years or older with operatively treated tibia fractures in Finland from 2000 to 2018 were included. The incidence of operatively treated proximal, diaphyseal, and distal tibia fractures per 100,000 person years by age, sex, mechanism of injury, and study year was calculated. Data were extracted from the Finnish National Hospital Discharge Register.
Results:
A total of 5996 proximal, 6874 diaphyseal, and 5658 distal tibia fractures were reported during the 18-year study period, resulting in incidences of 7.2/100,000, 8.1/100,000, and 6.9/100,000 person years for operatively treated proximal, diaphyseal, and distal tibia fractures, respectively. Over the study period, a clear change in fixation method in distal tibia fractures was found as plating became popular in the beginning of the 21st century. During the last 5 years of the study period, nailing and plating were equally used.
Conclusions:
Operatively treated proximal tibia fractures are most common among older females while diaphyseal fractures are most frequent in young male patients. Distal tibia fractures occur most often among middle-aged people.